Design of an Optical Foot printer Device According to Mechanical Principles for Diagnosing Flatfoot and Standardizing It for Female player in Gymnastic - Wahed, Bashaer Hashem Abdel; Neamah, Ali Hasan (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The sciences related to sports help improve athletic performance, with proper posture being essential for achieving balance and movement capability. The foot pressure measurement device is a vital tool for selecting gymnasts, as it measures the force exerted on the ground. There is a need for research on postural deformities and their impact on athletic performance, highlighting the importance of sports selection and choosing the right athletes to achieve desired results in various sports activities. The sciences related to sports help improve athletic performance, with proper posture being essential for achieving balance and movement capability. The foot pressure measurement device is a vital tool for selecting gymnasts, as it measures the force exerted on the ground. There is a need for research on postural deformities and their impact on athletic performance, highlighting the importance of sports selection and choosing the right athletes to achieve desired results in various sports activities. Materials and Methods the researcher used the experimental method with a one-group design, which aligns with the research problem and helps achieve the study's objectives. The researcher defined the research population as gymnasts aged 5 to 8, consisting of 5 athletes, and the sample represented the population using a comprehensive sampling approach. Results: The use of the electronic foot scanner has saved time and effort for both the teacher and the student in measuring the foot arch, and it had a positive effect on student engagement with the proposed device. It also clarified that the foot arch positively impacts the performance level of the athletes, as evidenced by the statistics utilized by the researcher in their work Conclusion1. The arch of the foot can be an indicator of overall body balance issues. 2. The device is easy to use and can measure arch height within a standard time frame